THE DIFFERENCE IN ADDITION OF BACK MASSAGE COMBINATION IN PREGNANCY EXERCISE IN IMPROVING QUALITY OF SLEEP IN THIRD TRIMESTER PREGNANT WOMEN - Arenza, Mezzi Wulandari; Tianing, Ni Wayan; Griadhi, I Putu Adiartha (Majalah Ilmiah Fisioterapi Indonesia; Vol 6 No 2 (2018): Majalah Ilmiah Fisioterapi Indonesia, 2018)
ABSTRACT Sleep disturbance in the third trimester pregnant women is caused by discomfort, an increasingly large abdominal condition, back pain, frequent urination, fetal movement, heartburn, cramps in the legs, tiredness, difficulty getting started, and physiological changes. Sleep disorders result in decreased quality of sleep. Pregnant women who have poor sleep quality are at risk of longer labor, cesarean delivery, premature birth, and even infant mortality. The aim of this research is to know the difference of pregnant exercise combination and back massage in improving the sleep quality of third trimester pregnant women. This research use experiment method with quasi experiment approach and research design is pre and post test with control design. Sample are 18 people, divided into 2 groups, 9 people in treatment groups given pregnancy exercise and back massage and 9 people in control group is given only pregnant exercise. Intervention is given 8 times. Pittsburgh Sleep Quality Index (PSQI) questionnaire used for measured of sleep quality. The result of different test of unpaired group, in the treatment group got difference of average 4,556 and control group got difference mean 2,333 with p=0,004 (p<0,05). These results showed that there was a significant difference between the treatment group and the control group in improving the sleep quality of the third trimester pregnant women. In conclusion, there are differences in the addition of back massage combination in pregnancy exercise intervention in improving sleep quality of third trimester pregnant women. Keyword : Pregnancy Exercise, Back Massage, Sleep Quality, Third Trimester.